A review of perovskite photovoltaic materials' synthesis and applications via chemical vapor deposition method - Liu, Xia (2020)
Perovskite photovoltaic materials (PPMs) have emerged as one of superstar object for applications in photovoltaics due to their excellent properties-such as band-gap tunability, high carrier mobility, high optical gain, astrong nonlinear response-as well as simplicity of their integration with other types of optical and electronic structures. Meanwhile, PPMS and their constructed devices still present many challenges, such as stability, repeatability, and large area fabrication methods and so on. The key issue is: how can PPMs be prepared using an effective way which most of the readers care about. Chemical vapor deposition (CVD) technology with high efficiency, controllability, and repeatability has been regarded as a cost-effective road for fabricating high quality perovskites. This paper provides an overview of the recent progress in the synthesis and application of various PPMs via the CVD method. We mainly summarize the influence of different CVD technologies and important experimental parameters (temperature, pressure, growth environment, etc.) on the stabilization, structural design, and performance optimization of PPMS and devices. Furthermore, current challenges in the synthesis and application of PPMS using the CVD method are highlighted with suggested areas for future research.